Pagkakaisa at pagbabago : ang patotoo ng United Church of Christ in the Philippines - Aoanan, Melanio La Guardia (Quezon City : New Day Publishers, 1996)
Creeds of the congregation of the United Church of Christ in the Philippines
In Tagalog
Includes bibliographical references and index.
Keywords: United Church of Christ in the Philippines -- Creeds